Versatility of the pedicled buccal fat pad flap for the management of oroantral fistula: a retrospective study of 25 cases - Park, Jinyoung (Maxillofac Plast Reconstr Surg, 2019)
PURPOSE: Maxillary bone grafts and implantations have increased over recent years despite a lack of maxillary bone quality and quantity. The number of patients referred for oroantral fistula (OAF) due to implant or bone graft failure has increased, and in patients with an oroantral fistula, the pedicled buccal fat pad is viewed as a robust, reliable option. This study was conducted to document the usefulness of buccal fat pad grafts for oroantral fistula closure. MATERIALS AND METHODS: We retrospectively studied 25 patients with OAF treated with a buccal fat pad graft from 2015 to 2018. Sex, age, OAF location, cause, duration, presence of systemic disease, smoking, previous dental surgery, and side effects were investigated. RESULTS: A total of 25 patients were studied. Mean patient age was 54.8 years, and the male to female ratio was 19:6. Causes of oroantral fistula were cyst enucleation, tumor resection, implant removal, bone graft failure, and extraction. Excellent results were obtained in 23 (92%) of the 25 patients. In the other two patients that both smoked, a small fistula was observed during follow-up. No recurrence of oroantral fistula was observed after 2 months to 1 year of follow-up. CONCLUSIONS: The incidence of oroantral fistula is increasing due to implant and bone graft failures. Oroantral fistula closure using a pedicled buccal fat pad was found to have a high success rate.